O circo dos Dias - Parigi, Fulvio Lenotti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
O Circo dos Dias is a production that involves techniques from theater, circus arts and video art. To carry out this vídeo, some research was made to understand how the theater and the circus could influence the video. In this course conclusion work the reader will follow the process of creating both the video and the soundtrack

O Circo dos Dias é uma produção que envolve técnicas de teatro, arte circense e videoarte. Para realização deste vídeo foram feitas pesquisas para entender como o teatro, e, o circo poderia influenciar no vídeo. Neste trabalho de Conclusão de Curso o leitor acompanhará o processo de criação tanto do vídeo quanto da trilha musical
Keywords: Videoarte; Circos; Palhaços; Clowns